2007
DOI: 10.1002/smj.581
|View full text |Cite
|
Sign up to set email alerts
|

Strategic alliance contracts: dimensions and determinants of contractual complexity

Abstract: In contrast to prior studies examining strategic alliances as discrete governance structures (e.g., alliances vs. M&A, equity vs. non-equity agreements), we investigate their particular contractual features. The analysis examines the dimensionality of the contractual complexity construct and investigates the determinants of firms' adoption of various contractual provisions. We find two underlying dimensions of contractual complexity, based upon the enforcement and coordination functions of different contractu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
610
2
12

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 566 publications
(642 citation statements)
references
References 60 publications
18
610
2
12
Order By: Relevance
“…As we noted in our description of the structural school of thought on inter-organizational coordination, joint-venture structures can facilitate coordination by providing robust authority structures and enforcement mechanisms, dedicated staff, and opportunities to devise structures and procedures that fit the purpose of the alliance (Gulati & Singh, 1998). Detailed contracts can help address coordination challenges (Mellewigt et al, 2007;Reuer & Arino, 2007) by specifying tasks, roles, and responsibilities (Carson et al, 2006;Mayer & Argyres, 2004); contingency plans and responses (Ring & Van de Ven, 1994), and information-sharing and feedback channels to ensure smooth operation. Forwardlooking firms are likely to weigh those benefits against the higher costs of both JVs and detailed contracts and to select more formal governance when their coordination needs are highest, such as in situations characterized by high task uncertainty and interdependence (Gulati & Singh, 1998;Mesquita & Brush, 2008), incompatibilities stemming from partner diversity (White, 2005), or high costs for coordination failure (Mellewigt et al, 2007).…”
Section: Alliance Designmentioning
confidence: 99%
See 1 more Smart Citation
“…As we noted in our description of the structural school of thought on inter-organizational coordination, joint-venture structures can facilitate coordination by providing robust authority structures and enforcement mechanisms, dedicated staff, and opportunities to devise structures and procedures that fit the purpose of the alliance (Gulati & Singh, 1998). Detailed contracts can help address coordination challenges (Mellewigt et al, 2007;Reuer & Arino, 2007) by specifying tasks, roles, and responsibilities (Carson et al, 2006;Mayer & Argyres, 2004); contingency plans and responses (Ring & Van de Ven, 1994), and information-sharing and feedback channels to ensure smooth operation. Forwardlooking firms are likely to weigh those benefits against the higher costs of both JVs and detailed contracts and to select more formal governance when their coordination needs are highest, such as in situations characterized by high task uncertainty and interdependence (Gulati & Singh, 1998;Mesquita & Brush, 2008), incompatibilities stemming from partner diversity (White, 2005), or high costs for coordination failure (Mellewigt et al, 2007).…”
Section: Alliance Designmentioning
confidence: 99%
“…18 Though they do not always frame the debate explicitly in coordination terms, some scholars have argued that partner-specific experiences will influence which coordination issues partners anticipate and which coordination mechanisms they use in those partnerships. Some of the mechanism for coordination that partners develop over time can become routines that are implemented informally (Reuer & Arino, 2007), but some will be formalized in contracts that effectively serve as -repositories of knowledge‖ distilling the lessons of past coordination failures Argyres, Bercovitz, & Mayer, 2007). For example, partners' experiences of misunderstandings resulting from poor informal communication in prior alliances may prompt them to formalize information-exchange provisions in their subsequent alliance contracts (Mayer & Argyres, 2004).…”
Section: Alliance Designmentioning
confidence: 99%
“…Such informational uncertainty refers to situations in which complete contracts cannot be formulated due to the impossibility of identifying possible future events affecting an exchange that could arise from environmental uncertainties (Weber & Mayer, 2014). The dynamic technological environment and unpredictable nature of R&D activities suggest that not all contingencies can be identified during the alliance formation process (Reuer & Arino, 2007). Finally, alliance formation is subject to substantive interpretive uncertainty, i.e., uncertainty stemming from alliance partners perceiving ambiguous information differently (Weber & Mayer, 2014).…”
Section: Contextmentioning
confidence: 99%
“…We develop a conceptual framework that is embedded in economic perspectives of network capitalism (Boisot & Child, 1996;Tung & Worm, 2001), organizational control theory (Ouchi, 1980) and theoretical developments on organizational culture (Cameron & Quinn, 2011) and alliance contracts and contractual complexity (Ariño & Reuer, 2006a;Reuer & Ariño, 2007). Our objective is to add to the academic dialogue about contractual aspects and culture within Asia Pacific innovation alliances.…”
Section: An Example Is the Recently Established Asia Pacific Innovatimentioning
confidence: 99%
“…In addition to the common set of antecedents, recent research has shown that variation in partnership governance can also be attributed to contractual complexity (e.g. Reuer & Ariño, 2007), a concept distinctively different to both goal incongruence and performance ambiguity.…”
Section: Contractingmentioning
confidence: 99%